Determination of desalination system pricing in Penjaringan Utara subdistrict, North Jakarta using HOMER simulation - Rimbawa, H. A. Danang; Nurrahman, Muhammad Irsyaad; Saragih, Gabriel Winandika (Institute of Computer Science (IOCS), 2025)
The coastal area of Muara Angke in North Jakarta grapples with significant challenges regarding access to clean water, compounded by limited energy availability. In 2024, a desalination project utilizing reverse osmosis (RO) technology was launched to address this issue, with a capacity to produce 320 liters of clean water per hour. A key feature of this initiative is its reliance on solar energy, which offers a sustainable solution to the region’s energy constraints. However, to ensure the project's long-term viability, it is essential to conduct an economic evaluation, particularly focusing on the cost of producing the desalinated water. This cost is intricately linked to the energy required to power the reverse osmosis (RO) system. Specifically, the Cost of Energy (CoE) plays a crucial role in determining the price of the desalinated water. To assess the economic feasibility of the solar-powered desalination system, HOMER simulation software was used to model the performance of the solar power system, considering factors such as solar energy potential, system capacity, and the financial costs of the solar infrastructure, including the solar panels, inverters, and battery storage. The simulation results reveal an annual energy production of 58,900 kWh and a CoE of Rp 575.55 per kWh, which directly influences the cost of water production, resulting in a price of Rp 17.27 per liter for the desalinated water. This study highlights the essential role of renewable energy sources in ensuring the sustainability of desalination systems and emphasizes the importance of accurate cost analysis to make such systems economically viable in coastal communities like Muara Angke. By integrating RO technology with solar energy, this initiative offers a promising approach to addressing water scarcity while reducing reliance on non-renewable energy sources, ultimately providing a long-term solution to clean water access.